ASEAN : opportunities and challenges facing a rising Chinese economy - Chong, Catherine Siew Keng (2009)
At the 5th anniversary of the East Asian Institute (EM), on 17 July 2002, Singapore Senior Minister (currently Minister Mentor) Lee Kuan Yew, in his speech entitled “China in Transition”, addresses on the development of China. In his speech, he noted that a rising China is both a competitor and a partner for the rest of East Asia. With its low unit cost of production and abundant supply of cheap and skilled labor makes China, an attractive base to relocate industries seeking to remain globally competitive. For ASEAN, China has initially more of a competitor for FDIs and export markets. As it grows, China has been a huge potential market for unfinished goods produced from ASEAN. China’s outbound FDI to ASEAN countries has also been rising gradually in the past few years. ASEAN countries have been exploring ways to gain new advantages and remain competitive. The ASEAN Charter, which provides a legal foundation and institutional framework for building up the regional integration, will be signed in October 2008. All ASEAN countries will promise in the Charter to create a single market and production base with effective facilitation for trade and investment in which there is free flow of goods, services and investment, and freer flow of capital. At the same time, ASEAN will continue to tap on China’s growth, engaging in win-win cooperation with China in international economic cooperation and competition amid economic globalization.